Synthesis, X-ray crystal structure, IR and Raman spectroscopic analysis, quantum chemical computational and molecular docking studies on hydrazone-pyridine compound: As an insight into the inhibitor capacity of main protease of SARS-CoV2 - Topal, Tufan; Zorlu, Yunus; Karapinar, Nazan (Elsevier, 2021)
The characterization and synthesis of 3-chloro-2-{(2E)-2-[1-(4-chlorophenyl)ethylidene]hydrazinyl}pyridine (CCPEHP) was investigated in our study. Mass and UV-visible spectra were recorded in chloroform solvent. The CCPEHP molecule containing pyridine and chlorophenyl rings and hydrazone group crystallized in the triclinic system and P-1 space group. FTRaman and FTIR spectra were performed in the solid state. The optimized geometry of CCPEHP was computed by DFT/B3LYP method with 6-311 G (d, p) and 6-31 G (d, p) levels. The computed vibrational analysis, electronic absorption spectrum, electronic properties, molecular electrostatic potential, natural bond orbitals analysis and other calculated structural parameters were determined by using the DFT/B3LYP/6-31 G (d, p) basis set. The correlation of fundamental modes of the compound and the complete vibrational assignments analysis were studied. The strong and weak contacts were identified by using Hirshfeld surface analysis. The molecular modeling results showed that CCPEHP structure strongly binds to COVID-19 main protease by relative binding affinity of-6.4 kcal/mol. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Vibrational spectroscopy; Density functional theory; COVID-19; X-ray diffraction